Online peer-to-peer support for persons affected by prostate cancer: a systematic review - Ihrig, Andreas; Haun, Markus W. (Patient education and counseling, 2020)
Objective - Little is known about online peer-to-peer support for persons affected by prostate cancer (PC) and its potential effects. - Methods - Our systematic review of the literature followed the PRISMA statement and revealed a total of 2372 records. Finally, 24 studies about online peer-to-peer support for persons affected by PC were selected for qualitative synthesis. Due to a lack of suitable quantitative results, the intended meta-analysis was not possible. - Results - Available studies were almost exclusively descriptive. Only one randomized controlled trial (RCT) included 40 PC survivors. In this study, quality of life improved in online support group (OSG) users and decreased in the control group. However, it returned to baseline in both groups after eight weeks. As a summary across all studies, OSGs play a significant role in patients’ treatment decision-making and for the social environment of PC patients. Information exchange in OSGs was predominant, but emotional and supportive content also had an important function. - Conclusion - Due to the inconsistent methodology and the lack of reporting standards, a synthesis from the available studies is very limited. - Practice Implications - Population-based studies should focus on the actual use of OSGs. The effectiveness of OSGs needs to be investigated in RCTs.
Gesehen am 05.11.2020